2002
DOI: 10.1128/iai.70.4.2010-2015.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Enterococcal Polysaccharide Antigen Gene ( epa ) Cluster Is Widespread in Enterococcus faecalis and Influences Resistance to Phagocytic Killing of E. faecalis

Abstract: In previous studies, we cloned a cluster of genes involved in polysaccharide biosynthesis (epa) from Enterococcus faecalis strain OG1RF and showed that this gene cluster mediated synthesis of a polysaccharide in Escherichia coli. Disruption of two open reading frames in the epa gene cluster of OG1RF generated two mutants, TX5179 and TX5180, which were attenuated in a mouse peritonitis model. In the current study, Western blotting was performed with serum from a patient with E. faecalis endocarditis and polysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 23 publications
(10 reference statements)
5
101
0
3
Order By: Relevance
“…1B) (26,27). Since both mutants lack the Epa polysaccharide (20), the different phenotypes suggest that other, as yet undefined differences exist between these mutants. For example, the gene product of orfd4 might be used in other pathways that are important for translocation, and/or some function of orfde6 may be partially complemented in E. faecalis by another gene(s).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1B) (26,27). Since both mutants lack the Epa polysaccharide (20), the different phenotypes suggest that other, as yet undefined differences exist between these mutants. For example, the gene product of orfd4 might be used in other pathways that are important for translocation, and/or some function of orfde6 may be partially complemented in E. faecalis by another gene(s).…”
Section: Discussionmentioning
confidence: 99%
“…1B) and that is important for virulence in mice and for resistance to phagocytosis and/or killing by polymorphonuclear leukocytes (7,20,(25)(26)(27). The epa gene cluster has been shown to be widespread among E. faecalis strains (20), and Epa is thought to be a species-specific polysaccharide (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated that the cell wallanchored pheromone-inducible aggregation substance (AS) and the enterococcal polysaccharide antigen (Epa) in E. faecalis are involved in resistance to neutrophil-mediated killing (73)(74)(75). However, the E. faecalis OG1RF strain used in the present study does not bear AS, arguing for alternative mechanisms of immune evasion, such as the downregulation of integrin 4 expression on the surface of neutrophils (76); alteration of the neutrophil properties rendering them nonresponsive to bacterial infections, as is the case during enterococcal sepsis in thermally injured patients and mice (66,68,69); and survival within immune cells such as macrophages and biofilm formation, which are well-characterized virulence attributes of enterococci (18,(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89).…”
Section: Discussionmentioning
confidence: 99%